Reading Public Romanticism - Magnuson, Paul (Book collections on Project MUSE., 2014)
Reading Public Romanticism is a significant new example of the linking of esthetics and historical criticism. Here Paul Magnuson locates Romantic poetry within a public discourse that combines politics and esthetics, nationalism and domesticity, sexuality and morality, law and legitimacy. Building on his well-regarded previous work, Magnuson practices a methodology of close historical reading by identifying precise versions of poems, reading their rhetoric of allusion and quotation in the contexts of their original publication, and describing their public genres, such as the letter.